Hirarkhi Visual sebagai Faktor Kesesatan Konsumen pada Desain Kemasan Samar Identitas - Julianto Julianto (Bina Nusantara University, 2011)
Packaging vague identity, is the packaging that does not give clear information about the contents of the packed product, in this case are specific to the product needs of the household / consumer products, often everyday, more obvious when you're shopping at the supermarket, sensation very stunning visual eye, the colors, images and shapes capable of stopping the views of prospective consumers in packaging that 'teasing', it was due to good aesthetic qualities, but in reality many packaging designs negligent in giving the perception of 'immediately' to the identity of the contents of the packed product , this issue becomes crucial because it can be misleading or wrong perception of users, by taking random samples of products circulating in the community, trying to describe and analyze a simple through the principle of Visual Communication Design, hoping the result will remind the designers more aware of packaging labels will set out the communication function in media packaging, to provide specific information with respect to visual hierarchy to yield a clear identity of the product packaged.